Chant et regard médusant – Maurice Carême : Médua - Tóth, Ágnes (Verbum – Analecta Neolatina, 2018)
The subject of this study is Médua, a short story by Maurice Carême that incorporates all kinds of features one can encounter in fantastic literature: unexpected, supernatural elements, madness, duplication, metamorphosis. The short story is analyzed from the point of view of how physical interactions and their representations appear in it, especially the face and the eyes. The desire to understand the inconceivable leads us to the question of artistic identification, the profession of writing. Artistic responsibility does not only entail joy but also fear. To illustrate this, the writer uses the mythological story of Medusa as an allegory for the transfixing and cathartic force of writing.